Effects of inspiratory muscle training in patients with hypertension: a meta-analysis - Zheng, ShuQi; Zhang, Qi; Li, ShuiYan; Li, Shilin; Yao, Qiuru; Zheng, Xiaoyan; Li, Gege; Zeng, Yuting; Chen, Ling; Chen, Shuping; He, Longlong; Zou, Jihua; et al. (Frontiers in Cardiovascular Medicine, 2023)
Objective To explore the effects of inspiratory muscle training (IMT) on hypertension and provide guidance for its clinical application as an auxiliary approach. Methods Articles published prior to July 2022 were searched in Cochrane Library, Web of Science, PubMed, Embase, CNKI, and Wanfang databases. Included were randomized controlled studies that used IMT to treat individuals with hypertension. The mean difference (MD) was computed using the Revman 5.4 software. In individuals with hypertension, the effects of IMT on systolic blood pressure (SBP), diastolic blood pressure (DBP), heart rate (HR), and pulse pressure (PP) were compared and studied. Results There were found to be eight randomized controlled trials totaling 215 patients. According to a meta-analysis, the IMT reduced the SBP (MD: −12.55 mmHg, 95% CI: −15.78, −9.33), DBP (MD: −4.77 mmHg, 95% CI: −6.00, −3.54), HR (MD: −5.92 bpm, 95% CI: −8.72, −3.12), and PP (MD: −8.92 mmHg, 95% CI: −12.08, −5.76) in patients with hypertension. In subgroup analyses, low-intensity IMT showed a better reduction in SBP (MD: −14.47 mmHg, 95% CI: −17.60, −11.34), DBP (MD: −7.70 mmHg, 95% CI: −10.21, −5.18). Conclusion IMT may become an auxiliary means to improve the four hemodynamic indexes (SBP, DBP, HR and PP) in patients with hypertension. In subgroup analyses, low-intensity IMT was more effective in regulating blood pressure than medium-high-intensity IMT. Systematic Review Registration https://www.crd.york.ac.uk/prospero/, identifier: CRD42022300908.